Treat and Clean: A pilot study in stain removal and mending of substandard thrift store donations - Mak, Wing Sem; McQueen, Rachel; Kozlowski, Anika (Proceedings of the 6th Product Lifetimes and the Environment Conference (PLATE2025), 2025)
The growing prevalence of textile waste, largely driven by the fast-fashion model, necessitates a shift towards a circular economy that prioritises the reuse of materials. In Canada, the textile donation landscape is primarily managed by charities and for-profit organisations, which often rely on public donations to generate revenue. Despite high donation rates, many items received by thrift stores are unsuitable for resale, creating challenges for organisations dependent on volunteer labour. This paper discusses the Treat & Clean pilot study, part of a larger investigation into the quality and type of clothing donations received in Canadian thrift stores. The project aimed to assess the feasibility of rejuvenating so-called "substandard" clothing through cleaning and repair techniques, allowing these items to be resold. In total 4946 textile items donated to two large non-profit thrift organisations at nine separate store locations within Alberta and Saskatchewan were sorted. A significant portion of the donations were deemed unfit for immediate resale. A subset of sorted items (N=2271) was analysed off-site and considered for the Treat & Clean pilot. The effectiveness of the pilot was evaluated by analysing the success of treatments (e.g., stain removal) and tracking the resale of treated items. Results indicate that enhancing the quality of donations through simple cleaning and repair methods can increase the likelihood of their sale, thereby promoting sustainability in local communities. This study highlights the importance of increasing consumer awareness regarding donation quality.